On Pandemics and «New Atlantis»: An Ethical and Legal Reflection on Science and Policy in the Context of the Covid-19 Crisis - Montalvo Jääskeläinen, Federico de (Razón y fe, 2020)
The public health crisis caused by Covid-19 disease has brought back to the public arena the old debate of the role of politics and science in decision-making processes. In this paper we analyze, in the context of the current pandemics, how politics has left a stellar role for science, either because science has anticipated in its proposals to politics, or because politics has opted for it as a premeditated strategy. The references to the opinion of scientists as a decision-making criterion or, furthermore, their presence as true spokesmen for authority have been so frequent. This means rediscovering science and health as instruments of power, in terms that remind us of what Foucault denounced almost fifty years ago with his Biopolitics.